Norfloxacin Nanocrystals Through Surfactant Assisted Grinding - de Paula Costa, Giovanna [UNESP]; Isquibola, Guilherme [UNESP]; Ferreira, Patrícia Osório [UNESP]; Porto, Maria Vitória [UNESP]; Magdalena, Aroldo Geraldo [UNESP]; Caires, Flávio Junior [UNESP] (FapUNIFESP (SciELO), 2024)
The innovative work shows a new strategy to modify the physicochemical properties of medicines and improve patients’ lives. The mechanochemical synthesis and characterization of the first Norfloxacin nanocrystal are described. In recent decades, nanotechnology has gained significant attention in the scientific field through the study of the design, formation and application of materials at the nanoscale level. In the pharmaceutical sector, nanotechnology has been the focus of studies on systems that allow increased bioavailability. The present work investigated the formation of pharmaceutical nanocrystals. Nanocrystals are crystalline nanoparticles ranging in size from a few nanometers to 1,000 nm, composed of 100% of the drug and stabilized by surfactants or polymeric stabilizers. They have a safe formulation and are well tolerated compared to conventional medicines. The drug used in this study was Norfloxacin, a broad-spectrum antibiotic that has low bioavailability. Several nanocrystallization techniques are found in the literature, among which the mechanochemical method stands out. Mechanochemistry is an approach that allows the reduction of particle size through the mechanical energy provided in the reaction medium. Thus, it was possible to obtain nanomaterials and explore the influence of surfactants in controlling the particle size and morphology of the materials obtained.
Keywords: mechanochemical; nanocrystal; Norfloxacin; surfactant assisted grinding